Importance of Indigenous Peoples’ lands for the conservation of Intact Forest Landscapes - Fa, J.E.; Watson, J.E.M.; Leiper, I.; Potapov, P.; Evans, T.D.; Burgess, Neil D.; Molnár, Z.; Fernández-Llamazare, Á,; Duncan, T.; Wang, S.; Austin, B.J.; Jonas, H.; et al. (Wiley, 2020)
Intact Forest Landscapes (IFLs) are critical strongholds for the environmental services that they provide, not least for their role in climate protection. On the basis of information about the distributions of IFLs and Indigenous Peoples’ lands, we examined the importance of these areas for conserving the world's remaining intact forests. We determined that at least 36% of IFLs are within Indigenous Peoples’ lands, making these areas crucial to the mitigation action needed to avoid catastrophic climate change. We also provide evidence that IFL loss rates have been considerably lower on Indigenous Peoples’ lands than on other lands, although these forests are still vulnerable to clearing and other threats. World governments must recognize Indigenous Peoples’ rights, including land tenure rights, to ensure that Indigenous Peoples play active roles in decision‐making processes that affect IFLs on their lands. Such recognition is critical given the urgent need to reduce deforestation rates in the face of escalating climate change and global biodiversity loss.